2017
DOI: 10.1080/13554794.2017.1380202
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of interictal epileptiform discharges in cognitive functioning in CEC syndrome with evolution into epileptic encephalopathy

Abstract: In epileptic encephalopathies (EE), interictal epileptiform discharges (IEDs) contribute to cognitive impairment. The EE process has been studied in a patient affected by epilepsy with occipital calcification and celiac disease (CEC syndrome) by combining the administration of brain area stimulus specific (visual and auditory) reaction times (RT) during continuous EEG monitoring with the off-line reconstruction of auditory and visual evoked potentials (EP). Visual RT and VEP were abnormal only if recorded conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Forty-one studies detailed the age of onset of epilepsy in those with CD/GS [11, 1418, 22, 3436, 39, 40, 45, 47, 5256, 58, 6064, 66, 71, 73, 7680, 82, 83, 87, 70, 71, 73, 7680, 82, 83, 87]. This gave a pooled mean age of onset of 12 ( n = 161).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-one studies detailed the age of onset of epilepsy in those with CD/GS [11, 1418, 22, 3436, 39, 40, 45, 47, 5256, 58, 6064, 66, 71, 73, 7680, 82, 83, 87, 70, 71, 73, 7680, 82, 83, 87]. This gave a pooled mean age of onset of 12 ( n = 161).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 79 studies included in this review, 30 detailed cases of CEC syndrome making it the best classified presentation of epilepsy in the context of CD and gluten sensitivity [10, 14, 17, 32, 34, 36, 44, 50, 52, 55, 60, 62, 64, 66, 7085]. Sixteen of these papers are case reports and 14 are retrospective or prospective case series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it has been found that epileptic encephalopathy (EE) activity itself can lead to cognitive adverse consequences and it will deteriorate over time [17]. The following conclusions are drawn medial temporal lobe epilepsy (MTLE) and EE itself will lead to exacerbation of seizure dependence, but not limited to the above two types; In addition, clinical trial data show that status epilepticus (SE) may be an independent state leading to seizures.…”
Section: The Effect Of Epileptogenic Process Itself On Cognitive Func...mentioning
confidence: 94%